Malignant Ureteral Obstruction: Functional Duration of Metallic versus Polymeric Ureteral Stents - Chow, Po-Ming (PLoS One, 2015)
BACKGROUND: Ureteral obstruction caused by extrinsic compression is often associated with intra-abdominal cancers. Internal drainage with ureteral stents is typically the first-line therapy to relieve such obstructions. Novel designs of ureteral stents made of different materials have been invented to achieve better drainage. In this study, we described the functional outcomes of a Resonance metallic ureteral stent (Cook Medical, Bloomington, Indiana, USA) in patients with malignant ureteral obstruction and compare the functional duration of Resonance stents with regular polymeric stents in the same cohort. METHODS: Cancer patients who received polymeric stents and subsequent Resonance stents for ureteral obstruction between July 2009 and November 2012 were included in a chart review. Stent failure was detected by clinical symptoms, imaging studies, and renal function tests. The functional durations of each stent were calculated, and possible factors affecting stent patency were investigated. RESULTS: A total of 50 stents were successfully inserted into 50 ureteral units in 42 patients with malignant ureteral obstruction. There were 7 antegrade stents and 43 retrograde stents. There were no major complications. Stent-related symptoms were similar in both kinds of stents. After polymeric stents were replaced with Resonance metallic stents, hydronephrosis subsided or remained stable in 90% (45/50) of the ureteral units. Serum creatinine decreased or remained stable in 90% (38/42) of these patients. The Resonance stent exhibited a mean increase in functional duration of 4 months compared with the polymeric stents (p<0.0001), and 50% (25/50) of the Resonance stents exhibited a significant increase in functional duration (more than 3 months). Pre-operative serum creatinine < 2 was associated with a substantial increase in stent duration. CONCLUSIONS: Resonance stents are effective and safe in relieving malignant ureteral obstructions after polymeric stents failure. Resonance stents can provide a longer functional duration than polymeric stents and should be offered as an option for internal drainage.